Taman Tematik Di Kota Pekanbaru Dengan Pendekatan Arsitektur Metafora - Lela Purnamasari; Yohannes Firzal; Wahyu Hidayat3 (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Thematic parks as recreation areas encourage arts and social community. The Thematic Park area in Pekanbaru has reached 15.65% of the 30% availability of public green open space that has the potential to be a Smart Park. This opportunity can be used as an alternative to present Smart Park which is suitable for children. The research method applied to the design of the Thematic Park as a Smart Park is thematic garden architectural principles. This can be completed using an effective and innovative architecture metaphor approach and formed into an expressive and functional visual form. The concept applied to the design of the Smart Park is related to Atomic Rutherford. The electrons in the atom are formed as educational buildings that are scattered in theregional order and linked to the skybridge as an application of electron orbitals. Meanwhile, the atomic nucleus is formed as a waterwork zone by utilizing the sloping contour on the Thematic Park area.Keywords: Thematic Park, Smart Park, Metaphor, Atom Rutherford